T. Rex vs. Ankylosaurus : prehistoric showdown - Jackson, Tom, 1972- (Dino duel, 2026)
"The T. Rex might be large and speedy, but the ankylosaurus has thick, armored skin. Read about these dinosaurs and who might come out on top in a fight"--